Improving Students’ Business Letter Writing through a Genre-Based Approach - Zalukhu, Atalisi; Sihite, Jubil Ezer; Hasanah, Uswatun; Cahyani, Aliya Noor (UIR Press, 2025)
Writing business letters is an essential skill for students in English for Specific Purposes (ESP) contexts, as it prepares them to engage in professional communication effectively. However, many students encounter difficulties in producing business letters that are structurally accurate, contextually appropriate, and linguistically formal. This study aims to improve students’ business letter writing through the implementation of a Genre-Based Approach (GBA). The research employed a classroom action research design conducted in two cycles, involving third-semester students of the accounting department of Institut Bisnis dan Komputer Indonesia. Data were collected through pre-tests, post-tests, observations, and students’ written works, which were assessed using a rubric covering content, organization, language use, and format. The findings revealed that students showed significant improvement in their ability to construct business letters, particularly in terms of understanding the communicative purpose, using appropriate formal expressions, and applying correct letter structure. The results indicate that the stages of GBA building knowledge of the field, modeling, joint construction, and independent construction were effective because they explicitly introduced students to the social purposes and generic structure of business letters, enabling them to internalize both the functional and linguistic features of the genre. This explicit scaffolding not only facilitated students’ understanding of how language operates within professional contexts but also enhanced their confidence and autonomy in producing formal written communication. In conclusion, the Genre-Based Approach proves to be an effective and pedagogically grounded strategy for improving students’ business letter writing skills in ESP classrooms.